Bank audits and examinations : a detailed, step-by-step program for CPA's, bank internal auditors, bank directors, and bank examiners - Savage, John H. (Boston : Bankers Pub. Co., 1973)
It discussed principal activities of financial institutions such as securities, mortgages and savings accounts. Thus it serves as a useful guide to a Director, internal auditor, a a public accountant or any other person who has to conduct an examination or an audit of a commercial bank.
kjo 15/01/2019
Loans
Keywords: Bank examination; Auditing; Programming